Equivalence Analysis in the Translation of Deutsche Welle (DW) News Texts from German into Indonesian (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is aimed at analyzing the degree of equivalence in the translation of Deutsche Welle (DW) news texts from German into Indonesian by applying Mona Baker’s theoretical framework. A qualitative descriptive method was employed, with four DW news texts and their Indonesian translations serving as the data source. The analysis focused on equivalence at the word level and above the word level, considering syntactic, lexical, cohesive, and communicative functional aspects of the text. The findings indicate that the degree of translational equivalence varies, ranging from high to low levels. The “equivalent” category was found to be dominant, accounting for 57.6%, suggesting that most translations were able to maintain the meaning and function of the source text. Meanwhile, the categories “less equivalent” (22.9%) and “non-equivalent” (19.5%) reflect shifts in meaning, loss of information, and inaccuracies in lexical correspondences and grammatical structures. These results highlight the challenges in maintaining full equivalence during translation.